Technical and clinical success of endoscopic closure of endoscopy related gastrointestinal (GI) perforations using clips in the United States - Azar, Riad R. (2012)
Prior investigators have reported that endoscopy related perforations can be successfully treated by endoscopic closure using clips. However, there is limited data on the success of this technique for perforations in the United States.